2016
DOI: 10.1371/journal.pbio.1002361
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Orb2 Amyloidogenesis and Blockade of Memory Consolidation

Abstract: Amyloids are ordered protein aggregates that are typically associated with neurodegenerative diseases and cognitive impairment. By contrast, the amyloid-like state of the neuronal RNA binding protein Orb2 in Drosophila was recently implicated in memory consolidation, but it remains unclear what features of this functional amyloid-like protein give rise to such diametrically opposed behaviour. Here, using an array of biophysical, cell biological and behavioural assays we have characterized the structural featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(126 citation statements)
references
References 79 publications
(125 reference statements)
3
123
0
Order By: Relevance
“…In another study, they found that Orb2 aggregation is similar to the aggregation of other proteins related to diseases (80). For example, they found the formation of toxic amyloid oligomers.…”
Section: Prion-like Conversion Is a Physiological Process Involving Nmentioning
confidence: 89%
See 1 more Smart Citation
“…In another study, they found that Orb2 aggregation is similar to the aggregation of other proteins related to diseases (80). For example, they found the formation of toxic amyloid oligomers.…”
Section: Prion-like Conversion Is a Physiological Process Involving Nmentioning
confidence: 89%
“…Toxicity is typical of amyloid oligomers. As discussed above for Orb2, the toxic effect might depend on the kinetics of the formation of the intermediate and its evolution into fibrils (80). The toxicity of mutant p53 oligomers would not kill the cell (similar to Orb2) but would perturb protein homeostasis, likely resulting in the release of misfolded proteins, which could interact with proteins from different compartments in the cell or even move into other cells in the tissue.…”
Section: Prion-like Aggregation Of Tumor Suppressors In Cancermentioning
confidence: 99%
“…Consistent with this, the N-terminus of Aplysia CPEB (as well as related domains from Drosophila and mouse orthologs) can confer prion-like behavior to heterologous fusion proteins. [134][135][136] For example, when ApCPEB N-terminus fusions with a constitutively active Glucocorticoid Receptor (GR) are expressed in yeast cells carrying a GR-responsive, b-gal reporter, it is possible to easily read out the activity state of the GR-fusion protein from the color of colonies (white when inactive and blue when active). In this assay the fusion proteins produces metastable blue and white colonies, switch from blue (active) to white (inactive) colonies at rates consistent with prion-like conformational transition.…”
Section: Molecular Properties Of Aplysia Cpeb In Vitro and In Yeastmentioning
confidence: 99%
“…150 Importantly, although Orb2 oligomeric complexes share biochemical features with pathological amyloids, the proposed Orb2 amyloids appear uniquely transient in nature in contrast to classical irreversible and pathological amyloid assemblies. 135 The inherent differences in the properties of the 2 isoforms also impinge on the domains of the isoforms specifically required for maintenance of LTM. Flies lacking the Q/N domain in Orb2A but not Orb2B show severe LTM impairment.…”
Section: Cpeb1 In Drosophila -Orb2mentioning
confidence: 99%
“…The peptide corresponding to residues 78-102 in TDP- 43 Ca chemical shift assignments were obtained (Fig. 8A,B).…”
mentioning
confidence: 99%